Early weight-bearing after ankle fracture surgery: a systematic review and meta-analysis of functional outcomes and safety - Chengjing Wang; Changqing Li (Journal of Orthopaedic Surgery and Research)
Abstract Background Early weight-bearing (EWB) following ankle fracture surgery represents a paradigm shift from traditional rehabilitation protocols. This systematic review and meta-analysis evaluated the efficacy and safety of early versus delayed weight-bearing following operative treatment of ankle fractures. Methods We systematically searched six databases (PubMed, EMBASE, Cochrane CENTRAL, Web of Science, CINAHL, PEDro) from January 2015 to February 2025. Twelve studies (1,847 participants) comparing early (≤ 2 weeks) versus delayed weight-bearing protocols were included. Primary outcomes included functional scores, pain, range of motion, and complications. Random-effects meta-analyses used standardized mean differences for continuous outcomes and risk ratios for dichotomous outcomes. Results Early weight-bearing demonstrated significant advantages in pain reduction (SMD: +0.32, 95% CI: 0.21–0.43) and ankle dorsiflexion (SMD: +0.38, 95% CI: 0.26–0.50). Patients with EWB returned to work 12.3 weeks earlier and achieved clinically significant pain reduction 6 weeks sooner than delayed weight-bearing patients. Complication risk favored EWB (RR: 0.89, 95% CI: 0.69–1.14), with fewer immobilization-related complications (DVT: 2.5% vs. 6.3%; CRPS: 1.8% vs. 4.7%). Weber B fractures, younger age (< 45 years), and absence of syndesmotic injury predicted optimal EWB outcomes. Diabetic patients showed enhanced benefits from early mobilization compared to delayed protocols. Conclusions Early weight-bearing following ankle fracture surgery results in superior functional outcomes and equivalent safety compared to delayed protocols. Implementation within two weeks post-surgery appears optimal, with benefits most pronounced in Weber B fractures and younger patients. Syndesmotic injuries and diabetes require individualized assessment for optimal rehabilitation timing.